Innovative Approaches to Practical Training of Legal Professionals - G. Cherusheva; Y. Bohdan (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The growing role of legal education in Ukraine is due to the development of Ukrainian society as a constitutional state, the need for legal regulation of social relations, and the protection of civil rights and freedoms. This largely depends on the modernization of the current legal education system to meet today's challenges in training specialists for professional activities in state authorities, justice, and law enforcement; specialists who clearly understand the values of a democratic society based on the rule of law, human rights, and freedoms in Ukraine. According to S.V. Kononenko, this is possible on the basis of "a comprehensive combination of such aspects as legal education, the formation of legal culture, legal behavior, and certain professionally important psychological characteristics of the individual. Unity in solving this task ensures the training of lawyers with high professional competence" [1, p. 72], will contribute to increasing their competitiveness in the labor market. The article reveals conceptual approaches to comprehensive practical training of legal professionals. Based on theoretical analysis and research of the experience of training lawyers in higher education institutions, the main competencies that form the basis of professional readiness of future specialists are identified. Particular attention is paid to the analysis of the main areas of practical training, in particular interactive methods of developing practical skills and abilities, professional and general abilities specified in the Standard of Higher Education of the first (bachelor's) level of specialty 081 Law [2]. Based on the results of the study, a comprehensive methodology for cross-cutting practical training was developed, which included a list of interactive methods (in the process of training, undergoing various types of practical training, internships within the framework of a legal clinic, volunteer legal education activities for students among schoolchildren, etc.), each of which has its own motives and decision-making factors.